HISTOPATHOLOGICAL CHANGES ON ETROPLUS MACULATUS (BLOCH, 1795) DUE TO ZINC EXPOSURE - Devi, Archana; Nandan, S.Bijoy (International Journal of Engineering Technologies and Management Research, 2018)
The contamination of the aquatic systems with heavy metals from natural and anthropogenic sources has become a global problem which poses serious threats to ecosystems and natural communities. Heavy metals get bio concentrated in organisms that may cause health problems in humans via the food chain. The heavy metal zinc causes most serious environmental contaminations and effects due to its rampant use. In this study sublethal effects of the heavy metal, zinc on the histopathological parameters in fresh water fish, Etroplus maculatus was investigated. The 96 hour LC50 value of zinc was determined by Probit analysis, that was found to be 12.4 mg/L. The liver and kidney samples were collected from fish was exposed to sublethal concentrations of zinc on 14th and 28thdays.The structural deformities observed in the liver tissue showed swelling of hepatocytes, vacuolar degeneration, necrosis, nuclear hypertrophy and cirrhosis with acute haemorrhage where as, kidney showed degenerated renal capsule and renal tubule, edema, necrosis and haemorrhage in the interstetium. The histpathological changes become prominent as the days and concentration of exposure increases. The study thus establishes that zinc is harmful to Etroplus maculatus even in sublethal concentrations and effective management strategies are to be evolved and implemented to protect our water bodies and the organisms from problems of heavy metal pollution.